Impact of fallow on soil health in Mokokchung district, Nagaland, India - Temjen, Wati; Singh, Maibam Romeo; Jungla, Tali (Journal of Environmental Engineering and Landscape Management, 2021)
Two sites were selected from the district of Mokokchung, Nagaland viz., Forest Regeneration Site (FRS) and Shifting Cultivation Site (SCS). At FRS, soil pH ranged from 5.00±0.13–5.50±0.04, soil moisture 35.44±1.09–53.39±0.84%, soil temperature 14.33±0.47–23.83±0.23 °C, soil organic carbon 2.20±0.08–3.03±0.02% and available nitrogen 424.48±6.73– 547.46±2.10 Kg/ha. At SCS, soil pH ranged from 5.94±0.24–6.53±0.02, soil moisture 30.32±2.64–45.72±0.98%, soil temperature 17.83±0.62–26.1±0.08 °C, soil organic carbon 1.67±0.29–2.34±0.08% and available nitrogen 324.16±8.42– 443.20±1.06 Kg/ha. Significant correlation between soil temperature, pH, soil moisture and available nitrogen was observed at FRS, while correlation of soil moisture and pH was observed at SCS. A total of 21 fungal species belonging to 13 genera were identified from the two sites. FRS had more fungal diversity than SCS. The genus Aspergillus was dominant in both the studied sites. The study observed the detrimental effect of the shifting cultivation on soil health and highlights the need for monitoring and rectification to preserve soil health.